Microwave-assisted hydrothermal carbonization of sago (Metroxylon spp) to hydrochar as potential catalyst for etherification of glycerol - Rambli, Jakaria; Quitain, Armando T.; Khezri, Ramin; Wan Ab Karim Ghani, Wan Azlina; Assabumrungrat, Suttichai; Kida, Tetsuya (Elsevier, 2025)
The sustainable management of agricultural waste is crucial for achieving global carbon neutrality. Sago (Metroxylon spp) waste is generated in large quantities during starch extraction and is often discarded improperly or burned openly, which leads to significant environmental degradation. In this study, we converted sago waste into valuable hydrochar through microwave-assisted hydrothermal carbonization at temperatures between 200 and 250 °C for 1 h. Proximate and ultimate analyses were performed, as well as analyses of bulk density, pH, thermogravimetric and surface, and structure using scanning electron microscopy and BET. Hydrochar produced at 200 °C had a higher yield (29.8 %) than that produced using conventional heating methods. It also had an enhanced fixed carbon content (22.1–26.4 % compared to 11.04 % in raw biomass) and reduced O/C (0.999–1.432) and H/C (0.007–0.117) ratios. This indicates improved carbonization and hydrophobicity. The BET surface area of the hydrochar increased with temperature, ranging from 57.9 to 179.8 m2/g, with the highest value being reached at 250 °C. SEM analysis revealed that lower temperatures preserved more of the original fibrous structure of the biomass, whereas higher temperatures resulted in greater porosity and surface roughness due to the progressive breakdown and reformation of biomass components. Fourier transform infrared analysis revealed that polar functional groups, such as hydroxyl, carboxyl and carbonyl, decreased at 200 °C, thereby enhancing the stability of the hydrochar. Microwave-assisted hydrothermal carbonization at 200 °C produced hydrochar with balanced properties, achieving 99 % glycerol conversion and 59.9 % glycerol tert-butyl ether selectivity, thereby outperforming commercial resin catalysts.